Effects of Exogenous Trans-Zeatin and Lovastatin on Abortion of Small Seeds in ‘Dawuxing’ Loquat (Eriobotrya Japonica Lindl.) - Hui Zhang; Yong-Qing Wang; Qun-Xian Deng; Zhi-Wu Yang; Cui-Ping Pan; Zhuo-Heng Chi; Lu Wen; Yun-Miao Yang (Agriculture, 2021)
The small seeds of loquat possess very rich and diverse genetic characteristics which can potentially serve as precious resources for plant breeding. However, they are often aborted during the seed development. Cytokinin, as an important signaling mediator, plays a pivotal regulatory role in seed development. However, the effects of exogenous cytokinin application on the development of loquat seeds are poorly understood. In this study, we analyzed the potential effects of exogenous cytokinin on the abortion of small seeds of loquat. Cytokinin (20 mg/L trans-zeatin) and cytokinin inhibitor (60 mg/L lovastatin) were sprayed on the fruits of ‘Dawuxing’ loquat during an early stage of fruit expansion. The clean water treatment was used as the control group. The results showed that exogenous trans-zeatin significantly increased the weight of small seeds, the levels of soluble sugar and starch, as well as peroxidase (POD) and superoxide dismutase (SOD) activities. It also promoted a substantial increase in the expression of POD- and SOD-related genes during the process of small seed abortion. Moreover, trans-zeatin treatment significantly increased the content of endogenous trans-zeatin in the small seeds, and this increase in content showed a trend opposite to that of control (CKA). Cytokinin dehydrogenase related genes were found to be down-regulated after trans-zeatin treatment. It was found that exogenous cytokinin inhibitor (lovastatin) treatment could induce the anti-stress reaction in the small seeds during the early stage of treatment by significantly increasing the activities of POD and SOD, and the weight of small seeds at the early stage of treatment was significantly lower than that of the control group, but reverted to the level of the control group during the late stage of the treatment. Therefore, a specific concentration of trans-zeatin treatment can promote the development of small loquat seeds, while cytokinin inhibitor (lovastatin) can significantly inhibit the development of small seeds during the early stage of treatment. In summary, this study reports for the first time that application of exogenous trans-zeatin could effectively promote the development of small loquat seeds by significantly increasing the metabolism of small seeds. The small seeds which contained rich and diverse genetic characteristics often aborted during seed development. Our study thus established a foundation for the rescue of new germplasm resources of loquat by promoting the development of small loquat seeds.